THE INFLUENCE OF AUDITOR’S INDEPENDENCE, COMPETENCE, WORK EXPERIENCE AND PROFESSIONAL SKEPTICISM ON AUDIT QUALITY - HAKIMAH, HANIFAH AZZAHRA (Jurnal Ilmiah Mahasiswa FEB, 2018)
Auditor as a profession is one of the front runners when it comes to upholding thequality of financial reporting and providing the broader public with reliable financialinformation. It certainly encourages the public accounting firm to improve the qualityof audit generated. This study aims to determine whether auditor’s independence,competence, work experience and professional skepticism affect audit quality.Quantitative method is used in this research. Questionnaires were given to 130 auditorswho work at the big five public accounting firms in Jakarta. The collected data werethen analyzed using the multiple regression analysis. The result of this study indicatesthat auditor’s independence, competence, work experience and professional skepticismhave positive influence on audit quality partially and simultaneouslyKeywords: audit quality, ethics, independence, competence, work experience andprofessional skepticism.